Best Cafe Assessment Information System Using the ARAS (Additive Ratio Assessment) Method in Soppeng Regency - Andi Muhamad Sabri; Sri Wulandari; Hendrawansyah; Amriadi (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2026)
The development of cafe businesses in Soppeng Regency has increased rapidly, but it has not been supported by an objective evaluation system in determining the best quality cafe. So far, cafe assessments are still subjective and unstructured, oftencausing dissatisfaction from consumers. This study aims to build the best cafe assessment information system using the ARAS (Additive Ratio Assessment) method that can assess cafe quality objectively and measurably based on the criteria of taste, price, comfort, and service. The ARAS method is used because it is able to manage various types of criteria both benefit and cost, and produce a final ranking of each alternative based on its contribution to the ideal solution. The system was developed using the Waterfall model and tested using the Blackbox method. Data collection techniques included observation, interviews, and literature studies. The results show that the system successfully displays the complete assessment process, from value input, normalization, contribution calculation, to ranking results and printed reports. The best cafe assessment information system built us-ing the ARAS method has proven effective in supporting a more accurate and transparent decision-making process.